Tour leader’s service attributes towards customer retention - Aishah Mohd Nor,; Noranira Maamin,; Anies Faziehan Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to identify the level of tour leaders’ service attributes towards customer retention. It also examines the most influence factors of tour leaders’ service attributes towards customer retention. The factors that affect customer retention was also investigated. The primary data were collected using a structured questionnaire with Malaysian outbound tourists who travelled by group package tour (GPT) to Asian and non-Asian countries and had an experienced a tour leader service. The results revealed that the service attributes of the tour leader are significant to customer retention. The findings also revealed that tour leaders’ professional attitude and ability, professional knowledge and personal integrity and Islamic Values were significantly positively affected towards Customer Retention. The result mentioned, if the tour leaders’ service attributes is high, it is likely that the customer retention will be increased. However, to sustain and create business repetition, the travel agency should improve the presentation and communication skills even though after carefully examine, presentation and communication ability independent variable need to remove from the initial model due it has the highest value nonsignificant probability value. Thus, travel agencies also need to pay special attention to the performances and attitudes of the tour leaders’ services to ensure long term growth and success of the firm. Keywords: Tour leader; service attributes; customer retention; customer satisfaction; group package tour; travel agency; outbound travel